2021
DOI: 10.3389/fneur.2021.745240
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Identification of Ferroptosis-Related Biomarkers and Therapeutic Compounds in Ischemic Stroke

Abstract: Background: Stroke is one of the most common deadly diseases with an estimated 780,000 new cases globally, of which ischemic stroke accounts for over 80% of all cases. Ferroptosis is a new form of programmed cell death that plays a vital role in many diseases, including ischemic stroke and heart diseases. The role of the ferroptosis-related gene in the diagnosis, prognosis, or therapy of ischemic stroke was not fully clarified.Methods: Ferroptosis-related differentially expressed genes (DEGs) in ischemic strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…These researches indicate that ferroptosis plays a key role in the progression and toxicity of stroke. Chen et al [105] analyzed and identified ferroptosis-related differentially expressed genes (DEGs) in ischemic stroke by bioinformatics, which provided more evidence for the important role of ferroptosis in ischemic stroke. NAC is considered as a potential therapeutic agent of ferroptosis.…”
Section: Ferroptosis In Strokementioning
confidence: 99%
“…These researches indicate that ferroptosis plays a key role in the progression and toxicity of stroke. Chen et al [105] analyzed and identified ferroptosis-related differentially expressed genes (DEGs) in ischemic stroke by bioinformatics, which provided more evidence for the important role of ferroptosis in ischemic stroke. NAC is considered as a potential therapeutic agent of ferroptosis.…”
Section: Ferroptosis In Strokementioning
confidence: 99%
“…Recently, increasing studies have focused on finding biomarkers of ferroptosis in multiple levels, including morphology, biochemistry, protein, and gene [ 21 ]. For example, Guozhong Chen et al [ 22 ] reported that MAP1LC3B , PTGS2 , and TLR4 could be potential ferroptosis-related biomarkers for IS via bioinformatics, and further explored potential therapeutic compounds, such as Zinc11679756 (Eltrombopag). However, exploring the reliable predictive gene pair biomarkers and specific regulatory details pertaining to ferroptosis in IS still be enormous challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we aim to systematically discuss the “ferroptosis in stroke” research from 2013 to 2021 by bibliometric analysis. The bibliometric analysis combines mathematical and statistical methods with data visualization ( Chen G. et al, 2021 ), to present the annual publications, countries/regions, institutions, journals, authors, and co-citation; to evaluate global patterns of collaboration between authors, institutions, and countries; and to determine the study trend and hotspot in “ferroptosis in stroke”.…”
Section: Introductionmentioning
confidence: 99%